In-vitro fractional flow reserve of coronary artery - Kwa, June Li Jun (Nanyang Technological University, 2021)
Currently in the medical industry, there are a few ways to diagnose aortic valve stenosis. Some of the methods include but not limited to: Echocardiogram, Electrocardiogram (EKG/EKG), or Coronary Computed Tomography Angiography (CCTA) scan, and Cardiac catherization. Methods such as Echocardiogram, Electrocardiogram might be able to confirm whether stenosis is present however, these methods cannot accurately determine the severity of the stenosis. CCTA is the most accurate method to determine level of stenosis in the coronary arteries. CCTA is however, an invasive procedure that is not a suitable procedure of some patients. The objective of this project is to explore the possibility of using a non-invasive method to measure the level of stenosis in the patient’s arteries using a in-vitro set up. In this project, we will be making use of 3 different 3D printed coronary arteries at the stroke volume of 71.6ml. After collecting the data, several pressure waveforms and cardiac cycle waveform were created, and we are able to use Fractional flow reserve (FFR) to determine the presence of stenosis. We are also able to conclude that FFR is a viable method for those who are unable to participate in invasive procedures.